Highlights of metal ion-based photochemical switches - Bianchi, Antonio; Delgado-Pinar, Estefania; Garcia-Espana, Enrique; Giorgi, Claudia; Pina, Fernando (Coordination Chemistry Reviews, 2014)
n/a
Times Cited: 0 Pina, Fernando/C-8161-2011 Pina, Fernando/0000-0001-8529-6848 0